ANALISIS CAPAIAN PERKEMBANGAN EMOSI PADA ANAK USIA 5-6 TAHUN DARI KELUARGA BERCERAI DI RA UMMUL MU’IN PATUMBAK - Rini Wulandari; Kamtini Kamtini (JIP: Jurnal Ilmu Pendidikan, 2025)
The purpose of this study is to determine the achievement of emotional development in children aged 5-6 years from divorced families at RA UMMUL MU'IN Patumbak. Penelitian ini dilatarbelakangi oleh problematika capaian perkembangan emosi pada anak usia 5-6 tahun dari keluarga bercerai di RA UMMUL MU”IN Patumbak. This study uses a descriptive qualitative research type with research subjects of 3 children, 3 parents, and 1 class teacher. The data collection techniques used were direct observation, structured interviews, and documentation. Data analysis used is data triangulation, by comparing data sources, looking for similarities and differences, and drawing conclusions. The results of the study indicate that the achievement of emotional development in children aged 5-6 years from divorced families at RA UMMUL MU'IN Patumbak can be achieved overall, where children who are victims of divorce can be cooperative with friends, can show tolerance, can express emotions in various situations, understand rules and discipline, and know manners.